2018
DOI: 10.2139/ssrn.3253467
|View full text |Cite
|
Sign up to set email alerts
|

Labor Market Returns to Education and English Language Skills in the People's Republic of China: An Update

Abstract: We reexamine the economic returns to education in the People's Republic of China (PRC) using data from the Chinese General Social Survey 2010. We find that the conventional ordinary least squares estimate of wage returns to schooling is 7.8%, while the instrumental variable estimate is 20.9%. The gains from schooling rise sharply with higher levels of education. The estimated returns are 12.2% in urban provinces and 10.7% in coastal provinces, higher than in rural and inland areas. In addition, the wage premiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Accordingly, this paper mainly discusses two scenarios representing China's typical migration patterns: inland‐coastal migration (scenario 1) and coastal‐inland migration (scenario 2). In the meantime, scholars have also identified that coastal developed regions have a higher skill premium of wage (or return to skills) than inland regions (Asadullah & Xiao, 2019, 2020; Whalley & Xing, 2014; Zou et al, 2009). Therefore, we can assume that return to skills ( η) in coastal regions is higher than that in inland regions.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Accordingly, this paper mainly discusses two scenarios representing China's typical migration patterns: inland‐coastal migration (scenario 1) and coastal‐inland migration (scenario 2). In the meantime, scholars have also identified that coastal developed regions have a higher skill premium of wage (or return to skills) than inland regions (Asadullah & Xiao, 2019, 2020; Whalley & Xing, 2014; Zou et al, 2009). Therefore, we can assume that return to skills ( η) in coastal regions is higher than that in inland regions.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Di Paolo and Tansel (2015) showed that knowledge of English and Russian are associated with higher earnings in Turkey. For the People's Republic of China, the estimated wage premium from good knowledge of English is about 30% (Asadullah & Xiao, 2019). For Poland, Liwiński (2019) found that advanced command of a foreign language increases wages by 11%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mastering foreign languages, apart from the fact it gives an advantage in recruitment to subsequent educational stages, is extremely valuable on the labour market. Research shows that the command of foreign languages among native employees is associated with higher earnings (Asadullah & Xiao, 2019;Di Paolo & Tansel, 2015;Liwiński, 2019). There is also a belief among Polish parents that it is difficult to learn a foreign language at school.…”
Section: Introductionmentioning
confidence: 99%
“…Gazzola and Mazzacani (2019) show that English language skills increase the probability of being employed for men in Germany, Italy and Spain and women in Germany and Italy, although French language skills have no significant impact. Asadullah and Xiao (2019) show that English language skills bring a wage premium in China. Foreman‐Peck and Zhou (2015) study small and medium‐size exporting firms in Europe and show the lack of investment in language skills in English native speaking countries.…”
Section: Related Literaturementioning
confidence: 99%